Motivation In Physical Education (PE) Learning Through Online System - Mohamad Da'i; Olivia Dwi Cahyani; Adi S (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
This study aims to determine the learning motivation of students in the Physical Education subject through online / online learning in the 2020/2021 academic year. This study used a descriptive survey method and a questionnaire for data collection. The subjects in this study were all students of class X at SMA Plus Al Fatimah Bojonegoro, totaling 112 students. The validity coefficient is 0.890 and the reliability is 0.891. The results of this study indicate that through the online learning system physical education subjects in class X SMA Plus AL Fatimah Bojonegoro academic year 2020/2021 the learning motivation of students is in the "high" category which is 14.29% (14 students), the "medium" category namely 73.21% (82 students) while those in the "low" category were 12.50% (16 students). Thus it can be concluded that through the online system students of class X / SMA Plus AL Fatimah Bojonegoro in the academic year 2020/2021 the learning motivation of Physical Education students is in the moderate category.